2017
DOI: 10.3354/cr01491
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding pitfalls in interdisciplinary education

Abstract: As the world's social-environmental problems increasingly extend across boundaries, both disciplinary and political, there is a growing need for interdisciplinarity, not only in research per se, but also in doctoral education. We present the common pitfalls of interdisciplinary research in doctoral education, illustrating approaches towards solutions using the Nordic Centre for Research on Marine Ecosystems and Resources under Climate Change (NorMER) research network as a case study. We provide insights and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is widely acknowledged that such an interdisciplinary approach is rather time consuming (Jones, 2010), as a common ground for analysis needs to be developed. This requires, next to developing a common credible framework, developing a common language and understanding of terms (Holt et al, 2017).…”
Section: Principles For a Framework For Multi-usementioning
confidence: 99%
“…It is widely acknowledged that such an interdisciplinary approach is rather time consuming (Jones, 2010), as a common ground for analysis needs to be developed. This requires, next to developing a common credible framework, developing a common language and understanding of terms (Holt et al, 2017).…”
Section: Principles For a Framework For Multi-usementioning
confidence: 99%
“…In lieu of that, we examined the literature on interdisciplinary research in an attempt to identify instruments able to measure student progress related to the areas noted above. In searching, we examined published instruments in related areas, identified skills perceived to be essential for the scientific workforce of the future (Begg et al, 2015); read about pitfalls and complexity in defining, fostering and assessing interdisciplinary skills (Holt et al, 2017); and, found an interdisciplinary collaboration framework by Carr (Figure 2), which represents how challenging it is to operationalize all of the constructs and variables associated with interdisciplinary research and career preparation in an efficient and sustainable evaluation program. Given the challenges listed above, we chose three major thrusts for our internal assessment and evaluation efforts to be able to track progress and meet NSF's annual reporting requirements.…”
Section: Our Methodologymentioning
confidence: 99%